Relationship between interaction parent-child with addictability rate and heterosexual orientation in students - Abbas Ali Hosseinkhanzadeh; Mahbobeh Taher; S Zahra Seyednuri; Ayda Yahyazadeh; Mahdi Esapour (Drug Control Headquarters, Research and Education Office, 2014)
Objective: the purpose of this study was to study relationship between interaction parent-child with addictability rate and heterosexual orientation in students. Method: The statistical population consisted of all students of Guilan University in 2012-2013 academic year, which among them a sample of 200 students were selected by random cluster sampling method and they completed preparation to addiction scale relationship between parent-child scale and attitude and heterosexual orientation before marriage. Findings: Correlation analysis indicated a significant negative correlation between addictability in female students and male students with relationship with father, and positive affect, interlace and communication subscales. The relationship between female students' addictability with relationship with mother and positive affect, hurt and confusion and communication subscales was observed significant negative correlation, also there is a significant negative relationship between male students' addictability with the relationship with mother. There is significant negative relationship between heterosexual orientations in male students with relation with father, positive affects and interlace. Results of regression analysis showed that relationship with father and relationship with mother can anticipate addict ability in female and male students. Conclusion: If parents cannot establish an appropriate and constructive interaction with their child cause child face with affection and emotional deprivation and this poor emotional and affection deprivation may cause he or she bring to the addict ability and heterosexual orientation.